Helminth driven gut inflammation and microbial translocation associate with altered vaccine responses in rural Uganda - Nassuuna, Jacent; Walusimbi, Bridgious; Natukunda, Agnes; Zirimenya, Ludoviko (npj Vaccines, 2025)
Vaccine responses are sometimes impaired in rural, low-income settings. Helminth-associated gut barrier dysfunction and microbial translocation (MT) may be implicated. We used samples from a trial of praziquantel treatment-effects on vaccine responses in Schistosoma mansoni (Sm)-endemic Ugandan islands, measuring intestinal fatty acid-binding protein 2 (I-FABP2), lipopolysaccharide-binding protein, anti-endotoxin core antibodies (EndoCab), soluble CD14 (sCD14) in plasma, and faecal lipocalin-2, occult blood (FOB), and calprotectin (fCAL), and evaluating their associations with baseline helminth infection, praziquantel treatment, and responses to BCG, yellow fever, typhoid, HPV, and tetanus-diphtheria vaccines. Sm associated positively with fCAL and FOB, hookworm with I-FABP2, and any helminth with EndoCab IgM, fCAL and FOB. Sm associated inversely with sCD14. Praziquantel treatment reduced all marker concentrations, significantly fCAL and FOB, implying that Sm-associated gut inflammation and MT is reversible. Associations of assessed markers with vaccine-specific responses were predominantly inverse. Interventions to improve gut barrier function may enhance vaccine responsiveness.